(untitled) (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Cohen’s cross trigonal ureteric reimplantation is the gold standard for surgical management of vesicoureteric reflux (VUR) in children with high success rate. The objective of this study was to evaluate and assess the outcome of open Cohen’s procedure in children with VUR. Methods: A retrospective review of all patients with VUR who underwent Cohen’s procedure between March 2010 and February 2020 was done. The following were recorded for each patient: age, sex, grade of reflux, operative time, outcome and complications. Results: The series consisted of 40 patients (25 girls and 15 boys) who underwent Cohen’s procedure with a mean age of 32 months (6 months to 8 years). Bilateral repairs were performed in 16 patients (40%) in the same setting and unilateral repair in 24 patients (60%). Twenty-two patients (55%) had grade IV VUR, 13 patients (32.5%) had grade V VUR and 05 patients (12.5%) had grade III VUR. Mean operative time for bilateral repairs was 249.4(200-290) minutes and 158.3(130-180) minutes for unilateral repair respectively. The mean length of hospital stay was 10.55 (7-15) days. Major complications included two persistent VURs, and one case of bladder hematoma. Postoperative ultrasound abdomen in all patients and micturating cystourethrogram in few patients was obtained, in which 38 patients (95%) had normal study. Conclusion: Cohen’s uretric reimplantation is a standard procedure in paediatric VUR. For better outcome, patient selection and refinement of operative technique should be pursued.